Fluorescent emission enhancement by aluminium nanoantenna arrays in the near UV. (26th May 2016) - Dorh, N; Sarua, A; Stokes, J; Hueting, N A; Cryan, M J
Abstract: In this paper, we demonstrate fluorescence enhancement of a laser dye, using aluminium nanoantenna arrays designed for the near UV range. A series of nanorod arrays were fabricated by focused ion beam milling then spin-coated with a dye with an intrinsic quantum yield (QY) in the range 0.5 to 0.6. Scanning confocal photoluminescence measurements of the arrays show up to 1.9× enhancement of the fluorescence signal compared to the reference on glass. The observed near UV fluorescence enhancement is affected by the relatively high intrinsic QY of the dye and coupling to an array mode. FDTD modelling predicts strong dependence of the emission on angle, with maximum emission at high angles with respect to normal. The model predicts that using a lens with a numerical aperture of 0.9 would lead to an enhancement of up to ∼6×.